Реконструкция S-системы гибридным алгоритмом клонального отбора и дифференциальной эволюции - Фефелов, А.А.; Литвиненко, В.И.; Таиф, М.А.; Вороненко, М.А. (Управляющие системы и машины, 2017)
Рассмотрено решение задачи реконструкции генной регуляторной сети, представленной в форме S-системы. Предложен гибридный алгоритм, основанный на методе клонального отбора. Проведены экспериментальные исследования влияния параметров гибридного алгоритма на качество решения задачи идентификации S-системы. На тестовых примерах проведен сравнительный анализ предложенного алгоритма с другими аналогичными вычислительными методами. Розглянуто рішення задачі реконструкції генної регуляторної мережі, представленої у формі S-системи. Запропоновано гібридний алгоритм, заснований на методі клонального відбору. Проведено експериментальні дослідження впливу параметрів гібридного алгоритму на якість виконання задачі ідентифікації S-системи. На тестових прикладах проведено порівняльний аналіз запропонованого алгоритму з іншими аналогічними обчислювальними методами. Purpose. The aim of this work is to develop an effective hybrid method for the reconstruction of the gene regulatory networks, which will increase the rate of convergence in solving the problem of the S-system optimizing. Method. We propose a hybrid method for reconstructing the GRN. This method is based on the hybridization technology, which allows combining the best qualities of the algorithm of clonal selection and the algorithm of differential evolution. Results. We propose a hybrid method of reconstruction GRN, allowing to increase the convergence rate and accuracy of the optimization algorithm to solve the problem of identification S-system. The S-system was applied, as a computational model. Parameters and structure were calculated by using the clonal selection algorithm and algorithm differential evolution. The gene expression profiles are used as input data. They were represented by time series of changes in the expression products concentration. The experiments have shown the negative effect of the differential evolution operators application such as selection and crossover. On the other hand, a significant positive effect of mutation operator is shown, which is used in the algorithm of the differential evolution.